2022
DOI: 10.5194/egusphere-2022-406
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-objective calibration of the Community Land Model Version 5.0 using in-situ observations of water and energy fluxes and variables

Abstract: Abstract. This study evaluate water and energy fluxes and variables in combination with parameter optimization of the state-of-the-art land surface model Community Land Model version 5 (CLM5), using six years of hourly observations of latent heat flux, sensible heat flux, groundwater recharge and soil moisture. The results show that multi-objective calibration in combination with truncated singular value decomposition and Tikhonov regularization is a powerful method to improve the current practice of using loo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Multi‐variate calibration evaluates model fluxes and stores more directly. Various studies have highlighted the value of detailed in‐situ observations of snow (Corbari et al., 2022; Kelleher et al., 2017; Sleziak et al., 2020), actual evapotranspiration (Stisen et al., 2018; Széles et al., 2020), soil moisture (Denager et al., 2023; Pleasants et al., 2023; Stisen et al., 2018), overland flow (Széles et al., 2020), or groundwater (Fowler et al., 2020; Kelleher et al., 2017; Pleasants et al., 2023) for improving model internal consistency in experimental catchments. As many catchments lack ground‐based measurements beyond streamflow, remote sensing‐based observations may provide an important and valuable source of information for hydrological data (Ali et al., 2023; Jiang & Wang, 2019) despite the challenges related to their observation uncertainty or spatiotemporal resolution (Beck et al., 2021; Chen et al., 2021; Mortimer et al., 2020; Sun et al., 2018; Zhang et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Multi‐variate calibration evaluates model fluxes and stores more directly. Various studies have highlighted the value of detailed in‐situ observations of snow (Corbari et al., 2022; Kelleher et al., 2017; Sleziak et al., 2020), actual evapotranspiration (Stisen et al., 2018; Széles et al., 2020), soil moisture (Denager et al., 2023; Pleasants et al., 2023; Stisen et al., 2018), overland flow (Széles et al., 2020), or groundwater (Fowler et al., 2020; Kelleher et al., 2017; Pleasants et al., 2023) for improving model internal consistency in experimental catchments. As many catchments lack ground‐based measurements beyond streamflow, remote sensing‐based observations may provide an important and valuable source of information for hydrological data (Ali et al., 2023; Jiang & Wang, 2019) despite the challenges related to their observation uncertainty or spatiotemporal resolution (Beck et al., 2021; Chen et al., 2021; Mortimer et al., 2020; Sun et al., 2018; Zhang et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…TOPMODEL (Beven and Kirkby, 1979;Niu et al, 2005), and Variable Infiltration Capacity (VIC; Liang et al, 1994) are the two most widely used runoff generation parameterizations (Sheng et al, 2017). It has been demonstrated that calibrating relevant parameters in LSMs leads to improved performance in the simulated runoff at site level (Denager et al, 2022), at the watershed scale (Hou et al, 2012;Huang et al, 2013;Liao and Zhuang, 2017), continent scale (Troy et al, 2008;Yang et al, 2019), and global scale (Yang et al, 2021;Xu et al, 2022a). The simulated runoff is then routed as streamflow to the outlet through the river network in RTMs (or river component in ESM).…”
mentioning
confidence: 99%